Effect of Tax Audit and Tax Collection on Tax Revenue - Rizki Indrawan (International Journal of Science, Technology & Management, 2021)
This study aims to determine how the implementation of tax audits and tax collection in increasing tax revenue which is expected to be able to contribute to national development. The population used is registered taxpayers at KPP Pratama Cibeunying in 2015-2019 and the samples in this study are taxpayers issued SKP and taxpayers issued STP. The results of this study indicate that the partial tax audit has a negative and significant effect on tax revenue and tax collection has a significant negative effect. Meanwhile, simultaneously tax audit and tax collection have a negative and significant impact on tax revenue.